TINDAK TUTUR MEMINTA DAN MENYARANKAN DALAM BAHASA BANJAR LOKSADO - Rissari Yayuk (Multilingual, 2016)
This research focuses on the directive speech acts in Banjar Loksado language. Thisresearch aims to describe the form of directive speech acts (requesting and suggesting)inloksado Banjar Language. This research uses pragmatic approach and descriptivemethod to describe directive speech acts of requesting and suggesting in Banjar Loksadolanguage. The method used in collecting data are direct observation, and the techniqueused are: recording and note taking technique. The result shows that the directive speechacts of requesting has linguistics politeness forms, such as: muhun ’please’, tulung’help’, and minta ’ask’. Mean while, the marker of directive speech acts of suggesting arehandaknya ’should’, baiknya ’ought’, and mun bisa ’if you can’.